2021
DOI: 10.7759/cureus.15998
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Migraine and Tinnitus: A Challenging Narrative

Abstract: Vestibular migraine (VM) is one of the most common types of episodic vertigo. Over the last 11 years, this disorder has been studied by both neurologists and otolaryngologists. Based on the clinical symptoms and previous migraine history, the Barany Society and the International Classification of Headache Disorders have created the diagnostic criteria for VM. Unilateral and pulsatile headache, phonophobia, photophobia, auras, and a previous history of migraine have been included in these criteria. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, García et al . ( 26 ) found the opposite, and this could be because migraine generates vasospasms in small arterioles of the cochlea and the labyrinth is widely known as one of the main contributing factors for the presence of tinnitus. The difference with Garcia’s study may be due to differences in sample sizes because migraine in the present study was evaluated as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…However, García et al . ( 26 ) found the opposite, and this could be because migraine generates vasospasms in small arterioles of the cochlea and the labyrinth is widely known as one of the main contributing factors for the presence of tinnitus. The difference with Garcia’s study may be due to differences in sample sizes because migraine in the present study was evaluated as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…One cross-sectional study showed that headache was associated with tinnitus, and the association was stronger for individuals reporting migraine with aura[ 11 ]. Ear injuries, central sensitization, and visual snow can cause tinnitus and may be related to the occurrence of migraines[ 12 , 13 ]. Migraine, tinnitus, anxiety and depression are prevalently comorbid disorders and have been frequently reported in patients with visual snow.…”
Section: Discussionmentioning
confidence: 99%
“…Tinnitus is common affecting approximately 15% of the population, and prevalence increases with age ( 110 , 111 ). Those with a recently diagnosed vestibular or ontological disorder are also at higher risk of being diagnosed with tinnitus ( 112 ), particularly Ménière’s disease and vestibular migraine (estimated prevalence of 49 and 39.6%, respectively ( 113 ),), for which tinnitus may be the first symptom of the vestibular disorder ( 114 ). Shared neural fiber connections between the cochlear and vestibular system, and changes in the hydrodynamics of inner ear fluids are thought to underlie this association, at least in Ménière’s disease ( 115 ).…”
Section: Understanding the Underlying Mechanisms Of Effectmentioning
confidence: 99%